Chronic central retinal artery occlusion: Clinical manifestations, ocular neovascular complications, and risk of stroke - Jae Ryong Song; Se Joon Woo (PLoS ONE, 2025)
Central retinal artery occlusion (CRAO) is a vision-threatening emergency that can lead to chronic ischemic complications. This retrospective cohort study investigated clinical characteristics, neovascular complications, and stroke risk in patients with chronic CRAO defined as the post-acute phase state characterized by FA-confirmed persistent retinal ischemia ≥1 month after acute onset. We reviewed medical records of 570 eyes initially diagnosed with acute non-arteritic CRAO between September 2003 and December 2024, with 289 eyes meeting inclusion criteria. Chronic CRAO was defined as persistent prolonged arm-to-retina or arteriovenous transit times on fluorescein angiography performed >1 month after symptom onset, and further classified as delayed perfusion or nonperfusion based on venous filling patterns. Among 289 patients, 215 eyes (74.4%) had acute CRAO with spontaneous reperfusion, while 74 eyes (25.6%) had chronic CRAO, including 55 eyes (74.3%) with delayed perfusion and 19 eyes (25.7%) with nonperfusion. Chronic CRAO patients were older with higher prevalence of systemic comorbidities. Previous stroke (43.2% vs. 26.0%, p = 0.009) and concurrent stroke (20.3% vs. 12.1%, p = 0.122) were more common in chronic CRAO patients compared to acute CRAO. Neovascularization of the iris occurred exclusively in chronic CRAO (32.4% vs. 0.0%, p < 0.001), with the nonperfusion group showing significantly higher rates of neovascularization of the iris (90% vs. 13%, p < 0.001) and neovascular glaucoma (68% vs. 9%, p < 0.001) compared to delayed perfusion group. Kaplan-Meier analysis revealed earlier onset of neovascularization in nonperfusion cases (median 1.6 months) with a 20-fold increased hazard ratio. Approximately one quarter of acute non-arteritic CRAO patients progress to chronic CRAO, which is associated with increased stroke risk and ocular neovascularization, particularly when retinal arterial nonperfusion persists. These findings emphasize the importance of fluorescein angiography monitoring and systemic evaluation in CRAO management.